Parental attitudes regarding the need for genetic services in a pediatric brain tumor survivorship program. Issue 2 (18th October 2020) - Zalan, Alice; Maga, Tara; Perpich, Melody; Pillay Smiley, Natasha; Weiss McQuaid, Shelly
Abstract: Pediatric brain tumor survivorship populations have not been typically offered genetic services as part of routine care. Genetic services can be defined as family history collection, genetic risk assessment for a patient and family members, and coordination of genetic testing. Prior research has focused on the integration of genetic services in the general pediatric oncology survivorship population and found a need for these services to be implemented. Gathering a family history and providing a genetic risk assessment have previously been determined to be an integral step in determining if an individual's cancer was due to a hereditary predisposition. The purpose of this study was to examine parental attitudes regarding the need for genetic services in their child's pediatric brain tumor survivorship clinic. Twelve semi‐structured interviews were conducted with parents participating in the Brain STAR (Survivors Taking Action and Responsibility) program at Ann and Robert H. Lurie Children's Hospital of Chicago. A grounded theory approach was used to code and analyze the results thematically. Five key themes were identified: participants' perceived benefits and barriers regarding receiving genetic services, desirable time for implementation of these services, relevance of family history, and their thoughts regarding reproductive risk. These results provide insight for genetics professionals regarding the need for genetic services in this population, and how to best implement them.